Development of new renewable energy hybrid system for simple home electricity purposes - Rahmatullah Kasim; Khairul Umurani (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2022)
The need for energy has now become a major problem that is increasingly complex in all countries in the world to support their economic growth. These various conditions require the need for new renewable energy that can answer these challenges. Wind energy and solar cells have become one of the solutions to reduce dependence on fossil energy. Wind energy and solar energy are actually the most promising sources of energy considering their sustainable nature and very large amounts to be used as electrical energy for lighting in simple people's homes. A wind turbine is a prime mover that utilizes wind energy to drive the turbine blades which are then transformed in the form of mechanical energy to rotate the turbine shaft. Solar energy is energy in the form of light and heat from the sun, which technology can be applied to a variety of energies, including solar thermal electrical energy. New and renewable energy with hybrid or combined systems for home-scale power plants is very much needed to ensure the continuity of the existence of electrical energy and efficiency. The combined and hybrid system models that have been developed and applied are hybrid solar cells and wind turbines.